1995
DOI: 10.1051/rnd:19950302
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of a dehydrated lucerne/barley diet (70:30) in defaunated, Isotricha-monoinoculated and mixed-fauna-inoculated rumen in sheep

Abstract: Summary ― Two adult Texel sheep fitted with permanent rumen fistulae were defaunated for 12 weeks in a preliminary experiment. They were then reinoculated with Isotricha sp for 11 weeks, and finally with a mixed fauna (Entodinium, Epidinium, Eudiplodinium and Isotricha) for 10 weeks. They were fed a diet composed of dehydrated lucerne (700 g/d), pelleted barley grain (300 g/d), grass hay (100 g/d) and wheat straw (50 g/d) in one daily meal. Isotricha and the ciliates of the mixed fauna developed rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…The protozoal population in heifers after refaunation from a previously defaunated state was well established by day 7 and reached 7.38 × 10 5 cells/mL by day 21, comparable with that found by Sénaud et al. () who re‐inoculated defaunated ruminants with Isotricha and ciliates of mixed fauna and found that the maximum concentration of protozoa was reached 9–17 days after inoculation. The maximum population then decreased for 2–3 days before stabilising.…”
Section: Discussionsupporting
confidence: 86%
“…The protozoal population in heifers after refaunation from a previously defaunated state was well established by day 7 and reached 7.38 × 10 5 cells/mL by day 21, comparable with that found by Sénaud et al. () who re‐inoculated defaunated ruminants with Isotricha and ciliates of mixed fauna and found that the maximum concentration of protozoa was reached 9–17 days after inoculation. The maximum population then decreased for 2–3 days before stabilising.…”
Section: Discussionsupporting
confidence: 86%